An Overview of Riding Styles Among Junior High School Students in Semarang City - Indarjo, Sofwan; Istiklaili, Fifti; Isniyati, Heni; Ardiansyah, Irman Syahrul; Yamini, Ismatul; Fadhil, Azhar Fauzan (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Background: It has been shown that underage individuals are more vulnerable to involvement in traffic accidents. In 2023, a total of 1,339 traffic accidents were documented in the city of Semarang. There were 1,515 traffic accidents involving 3,113 perpetrators with 17.5% (546) aged 5-20 years in 2024. The objective of this study was to identify the factors associated with the riding behavior of junior high school students in Semarang City. Methods: The present study was conducted as an observational analytical study employing a cross-sectional approach. A total of 447 subjects were selected as a sample for the study. The sampling technique used was cluster sampling. The data were collected via an online questionnaire and subsequently analyzed using the chi-square test and logistic regression. Results: The findings indicated that knowledge (p = 0.006), attitude (p = 0.001), and parental involvement (p = 0.009) were significantly associated with students' riding behaviors. Conclusion:The findings of this study indicate that educational and parental involvement are both critical factors in shaping the riding behavior of adolescent motorcyclists.